Pengolahan Produk Ikan Bandeng di Desa Tekolabbua Kecamatan Pangkajene Kabupaten Pangkep - Andi Tenri Abeng; Zulkifli Maulana (Universitas Muhammadiyah Parepare)
The purpose of this PKM activity is to increase partners' knowledge and skills in carrying out milkfish product processing activities in Tekolabbua Village, Pangkajene District, Pangkep Regency. Specific targets that will provide and increase the participation of all components of the community in making processed milkfish products into thornless milkfish, presto milkfish, and shredded milkfish. Mitra has the skills to do a business of milkfish products to become thornless milkfish, presto milkfish, and shredded milkfish. The methods used in achieving these objectives are: (1) Conducting counseling on processed milkfish products into thornless milkfish, presto milkfish, and shredded milkfish. The method used is the method of lectures, discussions and questions and answers, (2) conducting training to make milkfish products into milkfish without thorns, presto milkfish, and shredded milkfish. The method used is the method of discussion, question, and answer, demonstration, demonstration, and training. The planned activities to be carried out are (1) discussing the knowledge of making milkfish processed products into thornless milkfish, presto milkfish and shredded milkfish and marketing management, (2) conducting training to make milkfish processed products into thornless milkfish products. presto, and shredded milkfish. The results that will be achieved in the empowerment of farmer groups in the milkfish product processing business are formed independent farmer groups to improve better quality.